Exemplars: Medieval Manuscripts in Montreal and the McGill University Library Collection of Books of Hours - Virr, Richard (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2016)
The Books of Hours held by the McGill University Library were mostly acquired as exemplars of medieval books for the Library Museum begun by the university librarian, Dr. Gerhard R. Lomer, in 1920. This study documents their acquisitions in the context of the acquisition of other materials for the Library Museum until 1947, when Lomer retired. It examines the context in which the Library Museum was created: the precedent set by the King’s Library at the British Museum, the Book Production Gallery of the Victoria and Albert Museum, and the John Rylands Library in Manchester. In particular, the parallel with the Museum at the Art Association of Montreal established by F. Cleveland Morgan is noted. It also discusses three earlier Montreal collections that included Books of Hours: the Montreal Caxton Exhibition of 1877 and the private collections of Gerald E. Hart and J. B. Learmont. Finally, this study proposes that the Library Museum should be seen as a history of the book museum, one that traces book culture across time and civilizations.